PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN WEBQUEST DALAM UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI KELAS XI IPS SMA NEGERI 6 SURAKARTA - Lestari, Ambar Widya; Martono, Trisno; M.Si, Ak, Bandi (Jurnal Pendidikan Insan Mandiri, 2016)
The aim of the research is to produce learning model problem based learning using the webquest in validity and affectivity to be implemented in SMA Negeri 6 Surakarta in effort to increase the result study in economic subject for the students.The research was used Research and Development Approach (R&D). The procedure of the research was applied reffering to design and development research according to Borg and Gall that contained 6 steps of the development such as: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing. The internal validation of learning model problem based learning using the webquest was involved the experts of learning, the experts of learning media, the experts of material and practitioner such as the economic teacher in this school. Though, the external validation was done by tryout learning model problem based learning using the webquest that involved the students of XI IPS class. The subject of this research was the all of eleven grade social sciences SMAN 6 in academic year of 2014/2015 the total of the students was 80. In this reserarch, the sample technique was taken by saturated sampling technique that was the technique to decide samples whether all member of population became the samples. The analysis technique data was used descriptive analysis and statistic inferential analysis.The result of the research showed that: 1. The learning model problem based learning using the webquest was stated valid based on the validity test by the experts, 2. The learning model problem based learning based using the webquest was proved effective to be implemented in learning activity so that it could be to increase the economic study for students.Keyword: learning model, problem based learning, webquest, the result study of the students